Inclusion, innovation and excellence: Higher Education in South Africa and its role in social development - Crane, Soudien (South African Journal of Higher Education, 2016)
How does the higher education sector in South Africa, located here at the edge of the African continent and surrounded by its almost unique complexities of time, space and sociality work with and reconcile the demands for inclusion and excellence? How does it manage the extraordinarily difficult task of exploring, benefitting from and participating in the global knowledge revolution while simultaneously addressing the moral and practical questions of social inclusion? How does it manage to hold in sight and engage with the contradictory forces that arise out of globalisation and particularly the need to be located in the world and yet be relevant for the local? These issues lie at the heart of the challenge of thinking about the future of the South African university. They pose the question to the self-conscious South African University of how it wishes to imagine itself. Is its future to be like its North American and European counterparts, or does it have to create an autochthonous version of itself that is distinctly and uniquely African?